Chemical characteristics and irrigation suitability of mine pit water at an open-cast coal mine in northern Shaanxi - Hao BAI; Liyong JI; Guoqing LI; Bin LIU; Songyao LI; Li YAN (Shuiwen dizhi gongcheng dizhi)
In the arid and semi-arid middle reaches of the Yellow River in northwest China, an open-cast coal mine has adopted the use of pit water for ecological irrigation in dump reclamation areas, which is an effective approach for the pit water resource utilization. However, the irrigation water quality and the interactions between the pit water and soil in the long-term irrigation remain insufficiently understood. Field sampling, water chemical testing, and soil column leaching experiments in lab were conducted to analyze the mine pit water quality and the water-soil interactions during the irrigation process. The irrigation suitability of pit water was evaluated by using indicators such as sodium adsorption ratio, soluble sodium percentage, residual sodium carbonate, and permeability index. The results show that the water chemical type of the pit water is HCO3—Na, with Na+ as the main cation and \begin{document}${HCO}_3^- $\end{document}as the main anion. The water chemical composition is mainly influenced by cation exchange and mineral dissolution. Total dissolved solids are mainly derived from Na+, Cl−, \begin{document}${SO}_4^{2-} $\end{document}, and \begin{document}${HCO}_3^- $\end{document}. The pit water can be directly used for irrigation. During the leaching experiment, dissolution and cation exchange were evident, with a significant increase in Ca2+ concentration in the early leachate. As the leaching experiment progressed, the water chemical type of the leachate gradually evolved from HCO3—Ca type to HCO3—Na type; with the increase of leaching time, the cation exchange intensity in the leachate increased, and the irrigation evaluation indicators in the leachate showed an increasing trend, though remaining within acceptable irrigation thresholds. This study can provide a basis for the rational utilization of mine pit water.